1992
DOI: 10.1891/0047-2220.23.3.18
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation Counselors' Awareness of Client Alcohol Abuse Patterns

Abstract: In this article, we examined the extent of alcohol abuse among several groups of individuals with other disabilities. We then compared our results with rehabilitation counselors estimates of alcohol abuse in the same client groups. One hundred and thirty-four rehabilitation clients were administered the Michigan Alcoholism Screening Test (MAST) at the time of initial interview to determine their level of alcohol consumption and/or abuse. The results indicated that clients with chronic mental illness and those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Ingraham et al 19 found that rehabilitation counselors in state VR agencies were ill equipped to identify substance abuse problems in their clients with traumatic disabilities. However, only 2.9% of the European American clients and 1.6% of Hispanic clients were identified as having cooccurring AODA problems in FY 2005.…”
Section: Discussionmentioning
confidence: 99%
“…Ingraham et al 19 found that rehabilitation counselors in state VR agencies were ill equipped to identify substance abuse problems in their clients with traumatic disabilities. However, only 2.9% of the European American clients and 1.6% of Hispanic clients were identified as having cooccurring AODA problems in FY 2005.…”
Section: Discussionmentioning
confidence: 99%
“…However, practitioners in the field have traditionally used slightly higher cut-off scores than those suggested by Selzer. For example, Ingraham et al (1992) suggested that a score of 4-points and lower indicates no problem, a score of 5-7 indicates of a potential problem, and a score of 8 or higher indicates alcoholism. It has been reported that the MAST accurately measures "self-identified" alcohol-dependent people.…”
Section: The Michigan Alcoholism Screening Test (Mast) and The Macandmentioning
confidence: 99%
“…In spite of these opportunities, VRCs do not consistently screen and intervene with clients around issues of substance abuse. 1,2…”
Section: Introductionmentioning
confidence: 99%